THE EFFECTIVENESS OF MODERN DRESSING WITH A COMBINATION OF AFRICAN LEAF NANOPARTICLE HYDROGEL AND PAPUAN HONEY FOR GRADE II DIABETIC WOUND HEALING - Rolyn Frisca Djamanmona; Oktovina Mobalen (Poltekkes Kemenkes Semarang, 2022)
The combination of African leaf nanoparticle hydrogel (Vernonia amygdalina) and Papuan honey in modern dressing to heal wound in grade II diabetic patients can reduce the care day length and amputation risk for upper or lower extremity areas that are often affected and wounded in the event of hyperglycemia. Wound care is performed every 3 days for 20 days based on the physiological process in the proliferative phase of wound healing. The diabetic wound was assessed using the Bates Jensen Wound Assessment Tool (BWAT). The research was experimental with pre- and post-test control group design. The results showed that the 20-day wound care with this combination could reduce the BWAT score by 5.2, a sign of its effectiveness as compared to the control group reduction by 4.33. Conclusively, performing a modern dressing using this combination for 30-45 minutes every 3 days for 20 days was effective in accelerating the healing process of grade II diabetic wounds.